Prospects for development of culturally inclusive models for education: diagnostic classification models - Urrutia-Jorde, Matias (Frontiers in Education, 2025)
Diagnostic classification models (DCM) have been a recent topic of conversation in the development of educational materials. Specifically, there has been significant criticism of their validity and use within the educational system. For this reason, I identify avenues for the development of DCMs by taking a global perspective. Current literature on adapting pedagogy to culture is presented to consider multidimensional models, like DCMs, as useful tools for global development. This publication aims to present DCMs in a more accessible format, as well as illustrate that multidimensional models are useful for large scale data aggregation. I challenge criticisms that DCMs has failed to establish reliability and validity by looking at the foundation of the model. Although not all issues are resolved, DCMs are presented as practical tools for future research, and as prospects for educational development in low- and middle-income countries.